If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = -1(x + -4) Reorder the terms: 42 = -1(-4 + x) 42 = (-4 * -1 + x * -1) 42 = (4 + -1x) Solving 42 = 4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 42 + x = 4 + -1x + x Combine like terms: -1x + x = 0 42 + x = 4 + 0 42 + x = 4 Add '-42' to each side of the equation. 42 + -42 + x = 4 + -42 Combine like terms: 42 + -42 = 0 0 + x = 4 + -42 x = 4 + -42 Combine like terms: 4 + -42 = -38 x = -38 Simplifying x = -38
| -8-4n=-3n | | 30+4x+2+6x+8= | | 1.4y+2.2=0 | | 10=3u+1 | | -4(x-12)-2=6 | | 3y-2+2y+7-y= | | 8x^2+5=12x | | x+g=21 | | 4(-2y+3)= | | 119+9-3a=-7 | | 5x-1x+3=5 | | 8x-4=15x-18 | | 8=-7+y | | 10b^3+4b^2= | | 3-6b+13=26 | | Z^2+-9Z+18=0 | | Logs=0.06 | | 1520=38(p+10) | | -8-5x-4x=3x+4 | | 5s^2-16s=0 | | 11(-28)-20=28 | | 7-2d=4-6-3d | | 5(x-2)=4-(14+8x) | | 22-41= | | 8x-10x+3=0 | | 855=5x+855 | | log(x+2)=log(3x+3) | | 5x^21/10x^7 | | s*5-21=54 | | Z*Z-9z+18=0 | | 19(.1860465116)=x | | 2t+5=t |